Potential effects of growth regulator agents on antioxidant activity of two verities of faba bean (viciafabal.,) - REFAAT AHMED IBRAHIM SABER (International Journal of Pharma and Bio Sciences, 2016)
Faba bean (Vicia faba L.) as the most cultivated leguminous species in the world, is an excellent source of protein, dietary fiber, micronutrients and phytochemicals. A field experiment was conducted at Ghazala, Zagazig University, Sharkia Governorate during 2015, to study the effect of plant Growth Regulator such as; Gibberellic acid (GA3) and Inidol acetic acid (IAA) on antioxidant contents of two genotype seed extracts Nubaria 1 and Miser 3. Both two varieties were treated with both GA3 and IAA at two levels 50 and 100 ppm and 100ppmGA3 +100ppm IAA as foliar treatments. The Nubaria 1 seeds extracts have highest contents of phenolics (13.51, 13.64, 16.94, 17.97 and 20.53 GAE/g and flavonoid (8.07, 8.06, 9.12, 10.28 and 11.86 mg/QE/g, respectively. Also genotype seed extracts (Nubaria 1) has have highest antioxidant capacity (82.82% DPPH). Plant growth regulators such as GA3 and IAA are improving biosynthesis of phenolics and flavonoids, therefore improve antioxidant capacity and nutrition value of seeds.